NEW SPECIES OF ORECTURUS HUMES, 1992 (COPEPODA: SIPHONOSTOMATOIDA: ASTEROCHERIDAE), FROM CUBA - Varela, Carlos (2011)
This paper describes a new copepod species belonging to the genus Orecturus found in association with the octocoral Eunicea mammosa in La Habana province. This species shares several similarities with O. grandisetiger and O. bahiensis such as the presence of three setae in the exopodite of the antenna, two distal and one lateral. Nevertheless, differences include lack of triangular lobes in the 5th segment, antennule with 17 segments, and short 3-segment setae of almost the same length.